2019
DOI: 10.1177/1055665618820753
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-Year Follow-Up of 160 Consecutive Individuals Born With Unilateral Cleft Lip or Cleft Lip and Alveolus Treated by the Oslo Cleft Lip and Palate Team

Abstract: Objective: Describe patients born with unilateral cleft lip with or without cleft alveolus (CL±A) in relation to cleft severity and laterality, gender, associated anomalies and syndromes, number and type of lip- and nose operations, and time of alveolar bone graft (ABG) treatment in relation to dental status in cleft area. Materials and Methods: Patients included 220 children born with unilateral CL±A, born between 1988 and 1997 referred to the Oslo Cleft Lip and Palate Team. The data were collected retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…A retrospective cohort study including 220 child born with unilateral CL+A, concluded that the findings of this study provide a reference for morphologic variations in CL+A and insight into the surgical burden of care until the age of 18 years. These results are consistent with the results of our study on the influence of the management of cleft lip and palate on the quality of life of children and adolescents [38].…”
Section: Orofacial Functions and Quality Of Lifesupporting
confidence: 93%
“…A retrospective cohort study including 220 child born with unilateral CL+A, concluded that the findings of this study provide a reference for morphologic variations in CL+A and insight into the surgical burden of care until the age of 18 years. These results are consistent with the results of our study on the influence of the management of cleft lip and palate on the quality of life of children and adolescents [38].…”
Section: Orofacial Functions and Quality Of Lifesupporting
confidence: 93%
“…This may have several important ramifications on and nasolabial aesthetic outcomes. However, it is important to note that other studies that have based ‘severity’ on involvement of the palate in the cleft and completeness of the cleft, rather than lip tissue hypoplasia have not replicated the findings by Chong et al 28–30 …”
Section: Discussionmentioning
confidence: 96%